2007
DOI: 10.1111/j.1464-410x.2007.06734.x
|View full text |Cite
|
Sign up to set email alerts
|

The expression of vascular endothelial growth factor is associated with the risk of cancer progression after radical prostatectomy

Abstract: OBJECTIVE To analyse the prognostic value of vascular endothelial growth factor (VEGF) in men with clinically localized prostate cancer. PATIENTS AND METHODS Paraffin wax‐embedded sections from the radical prostatectomy (RP) specimens of 40 men operated for clinically localized prostate cancer were used to build tissue microarrays. Of these patients, 17 had cancer progression and bone metastases after RP (group 1), and 23 remained free‐of‐tumour recurrence after RP (group 2). VEGF‐A expression was examined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
3
19
0
1
Order By: Relevance
“…Strong immunohistochemical staining was observed at the periphery of tumor nodules. In our tissue microarray this area might not always be included which could explain this differ- 49,50 In the same line the role and expression pattern of bFGF in the development and progression of PC in the literature is controversial. Cronauer et al 51 reported that bFGF is mainly expressed in carcinomatous areas whereas Trojan et al 52 found a significantly stronger expression in non-tumerous tissue compared with carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Strong immunohistochemical staining was observed at the periphery of tumor nodules. In our tissue microarray this area might not always be included which could explain this differ- 49,50 In the same line the role and expression pattern of bFGF in the development and progression of PC in the literature is controversial. Cronauer et al 51 reported that bFGF is mainly expressed in carcinomatous areas whereas Trojan et al 52 found a significantly stronger expression in non-tumerous tissue compared with carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, some studies have explored its prognostic significance in prostate cancer (19)(20)(21)(22)(23). Furthermore, tissue hypoxia is also a critical factor during the establishment of tumor angiogenesis and has been associated with increased tumor cell migration, metastasis, and poor patient outcome (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…El patrón de marcaje de VEGF es controversial como factor pronóstico para la evolución del CaP [21][22][23][24][25] , pero podría ser de utilidad en el diagnósti-co diferencial entre HPB y CaP cuando las biopsias sean dudosas, ya que el patrón de marcaje de VEGF de las células glandulares es diferente entre la cé-lulas malignas y las hiperplásicas (Figuras 1 y 2).…”
Section: Discussionunclassified